Giving attention to the oldies: redescription of Meterginus basalis (Arachnida: Opiliones: Cosmetidae) with some notes on the genitalia - Andrés F. García; Brittany Damron (Revista Mexicana de Biodiversidad)
Meterginus Pickard-Cambridge, 1905 is a Neotropical genus of harvestmen with 17 known species. In this work we present a redescription of Meterginus basalis Pickard-Cambridge, 1905 (type species of the genus) including the first scanning electron microscopy (SEM) images of the male genital. Additionally, images of the female ovipositor and a map with the distribution of Meterginus in Central America are given.